Law on Overseas Representative Missions of the Socialist Republic of Vietnam - The National Assembly (2009)
This Law provides for the functions, tasks, powers and organization of overseas representative missions of the Socialist Republic of Vietnam (below referred to as representative missions) and the state management of representative missions